Desafio XIV para trompete e piano de Marlos Nobre: uma abordagem interpretativa - Amaral, Gerson Frances do (2013)
This work suggests interpretative possibilities to the trumpet part of the piece “Challenge XIV” for Trumpet and Piano (or Strings) Opus 31 14 bis. The choice of this piece was made due to its relevance of a repertoire of Brazilian music for trumpet and also for its originality on interpretation and performance. This research was developed from a revision of a directed bibliography and also from an analisys of the performance elements: articulation, dynamics, tempo and phrasing.